CGHMaastricht
New member
- Joined
- Sep 16, 2016
- Messages
- 6
Trouble simplifying fcn: show that (f(x+h)-f(x))/h <=> -1/(x(x+h)) when f(x) = 1/x
Hi, I am studying economics mathematics but really struggle with my simplifications, especially when fractions are involved.
I need to show that (f(x+h)-f(x))/h <=> -1/(x(x+h)); when f(x) = 1/x (or x^-1)
So to put that in the function;
Demonstrate:
(((x+h)^-1)-x^-1))/h <=> -1/(x(x+h))
So far I (think) I can get the left hand side to:
1/(h(h+x)) - 1/(hx)
But am stuck as to how to take it further
Any help would be much appreciated!
Hi, I am studying economics mathematics but really struggle with my simplifications, especially when fractions are involved.
I need to show that (f(x+h)-f(x))/h <=> -1/(x(x+h)); when f(x) = 1/x (or x^-1)
So to put that in the function;
Demonstrate:
(((x+h)^-1)-x^-1))/h <=> -1/(x(x+h))
So far I (think) I can get the left hand side to:
1/(h(h+x)) - 1/(hx)
But am stuck as to how to take it further
Any help would be much appreciated!